2019
DOI: 10.1155/2019/1234263
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Improves the Wound Healing Potential of Mesenchymal Stem Cells through Paracrine and Metabolism Alterations

Abstract: Chronic and acute nonhealing wounds represent a major public health problem, and replacement of cutaneous lesions by the newly regenerated skin is challenging. Mesenchymal stem cells (MSC) and platelet-rich plasma (PRP) were separately tested in the attempt to regenerate the lost skin. However, these treatments often remained inefficient to achieve complete wound healing. Additional studies suggested that PRP could be used in combination with MSC to improve the cell therapy efficacy for tissue repair. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 44 publications
2
72
0
2
Order By: Relevance
“…Gabrielyan et al described a higher chemoattractive potential of HCM compared to pure VEGF (200 ng/mL), indicating the synergistic effects of the proteins in HCM [24]. Our results showed that proteins and cytokines are present in PL but not in HCM and ATE and stimulate cell proliferation, which is in line with the results from Herasant et al, who described an improved wound healing potential of MSCs in combination with platelet-rich plasma in mice [60].…”
Section: Discussionsupporting
confidence: 92%
“…Gabrielyan et al described a higher chemoattractive potential of HCM compared to pure VEGF (200 ng/mL), indicating the synergistic effects of the proteins in HCM [24]. Our results showed that proteins and cytokines are present in PL but not in HCM and ATE and stimulate cell proliferation, which is in line with the results from Herasant et al, who described an improved wound healing potential of MSCs in combination with platelet-rich plasma in mice [60].…”
Section: Discussionsupporting
confidence: 92%
“…Other investigations have used autologous or allogenic ADSCs in the treatment of Crohn's disease, critical limb ischemia, diabetic foot ulcers, and burns [63,[79][80][81][82]. In combination with fat or platelet-rich lysate, skin engraftment, and reconstitution have been improved in human and animal models [83][84][85]. Additionally, platelets lysate appeared to support ADSC proliferation and differentiation in vitro and might replace the use of fetal bovine serum during cell expansion [86].…”
Section: Adscs Advancements In Skin Therapymentioning
confidence: 99%
“…In addition, the roles of individual cells that can be present in PRP treatment vials will be discussed along with detailed information on their effects on tissue regenerative processes. Furthermore, recent advances in understanding PRP bioformulations, platelet dosing, the specific roles of particular leukocytes, and the effects of PGF concentrations and cytokines on mesenchymal stem cell (MSC) trophic effects [ 10 ] will be described, including the pivotal roles of PRP in targeting different cells and tissue environments following cell-signaling and paracrine effects [ 11 ]. Likewise, we will discuss PRP mechanisms related to inflammation and angiogenesis in tissue repair and regenerative processes.…”
Section: Introductionmentioning
confidence: 99%